Incident atrial fibrillation and the risk of fracture in the cardiovascular health study. Issue 2 (February 2017) - Wallace, E.; Siscovick, D.; Sitlani, C.; Dublin, S.; Mitchell, P.; Robbins, J.; Fink, H.; Cauley, J.; Bůžková, P.; Carbone, L.; Chen, Z.; Heckbert, S.
Abstract Summary In this prospective cohort of 4462 older adults, incident atrial fibrillation (AF) was not statistically significantly associated with subsequent risk of incident fracture. Introduction AF is associated with stroke, heart failure, dementia, and death, but its association with fracture is unknown. Therefore, we examined the association of incident AF with the risk of subsequent fracture in the Cardiovascular Health Study (CHS) cohort. Methods Of the CHS participants aged ≥65 years, 4462 were followed between 1991 and 2009, mean follow-up 8.8 years. Incident AF was identified by annual study electrocardiogram (ECG), hospital discharge diagnosis codes, or Medicare claims. Fractures of the hip, distal forearm, humerus, or pelvis were identified using hospital discharge diagnosis codes or Medicare claims. We used Cox proportional hazard models to estimate hazard ratios (HRs) and 95 % confidence intervals (CIs) for the association between incident AF (time-varying) and the risk of subsequent fracture. We also evaluated whether AF was associated with risk of sustaining a fall. Results Crude incident fracture rate was 22.9 per 1000 person-years in participants with AF and 17.7 per 1000 person-years in participants without AF. Individuals with incident AF were not at significantly higher risk of hip fracture (adjusted HR = 1.09, 95 % CI 0.83–1.42) or fracture at any selected site (adjusted HR = 0.97, 95 % CI 0.77–1.22) or risk of sustaining a fall (adjusted HR = 1.00, 95 % CI = 0.87–1.16) compared with those without AF. Conclusion In this cohort of older, community-dwelling adults, incident AF was not shown to be associated with falls or hip or other fractures.